Variant Purification of an Allogeneic Bone Block - Jonas Lorenz; Markus Schlee; Sarah Al-Maawi; Poju Chia; Robert A. Sader; Shahram Ghanaati (University of Zagreb. School of Dental Medicine, 2017)
Objective: This short communication reports on a histological analysis of the composition of the commercially available Maxgraft® allogeneic bone block. Materials and Methods: Based on previously published, easily applicable histological methods, blanc samples of the Maxgraft® allogeneic bone block have been decalcified, dehydrated and embedded in paraffin before histological and histochemical staining. Afterwards, the slides were evaluated for their material characteristics, such as the bone matrix structure and other components, including collagen or cells/cell remnants. Results: The results show that this bone block exhibits a trabecular structure with lamellar sub-organization. Additionally, cellular remnants within the osteocyte lacunae and at the outer trabecular surfaces reside together with remnants of the former inter-trabecular fatty and connective tissue, i.e., collagenous structures and connective tissue cells or cell remnants. Conclusion: Consistent with a previous study on this topic, the data presented here demonstrate that some of the certified purification techniques might not allow for the production of allogeneic materials free of organic cell and tissue components.